Central Venous Catheter-Related Bloodstream Infection with Kocuria kristinae in a Patient with Propionic Acidemia - Masato Kimura; Eichiro Kawai; Hisao Yaoita; Natsuko Ichinoi; Osamu Sakamoto; Shigeo Kure (Case Reports in Infectious Diseases)
Kocuria kristinae is a catalase-positive, coagulase-negative, Gram-positive coccus found in the environment and in normal skin and mucosa in humans; however, it is rarely isolated from clinical specimens and is considered a nonpathogenic bacterium. We describe a case of catheter-related bacteremia due to K. kristinae in a young adult with propionic acidemia undergoing periodic hemodialysis. The patient had a central venous catheter implanted for total parenteral nutrition approximately 6 months prior to the onset of symptoms because of repeated acute pancreatitis. K. kristinae was isolated from two sets of blood cultures collected from the catheter. Vancomycin followed by cefazolin for 16 days and 5-day ethanol lock therapy successfully eradicated the K. kristinae bacteremia. Although human infections with this organism appear to be rare and are sometimes considered to result from contamination, physicians should not underestimate its significance when it is isolated in clinical specimens.